Towards the mechanism of electrochemical activity and self-healing of 1 wt% PTSA doped polyaniline in alkyd composite polymer coating: combined AFM-based studies. Issue 23 (16th February 2016) - Li, Jing; Huang, Hui; Fielden, Matthew; Pan, Jinshan; Ecco, Luiz; Schellbach, Carsten; Delmas, Grégory; Claesson, Per Martin
Abstract : The mechanisms of electrochemical activity and the self-healing properties of a composite alkyd coating with 1 wt% PTSA doped polyaniline were investigated. Abstract : A composite solvent-borne alkyd coating with 1 wt% p -toluene sulfonic acid (PTSA) doped polyaniline (PANI) was prepared. The mechanisms of electrochemical activity and self-healing properties of the composite coating were investigated by in situ atomic force microscopy (AFM), intermodulation AFM (ImAFM), electrochemical controlled (EC)-AFM combined with cyclic voltammetry (CV), Kelvin force microscopy (KFM), and Fourier transform infrared spectroscopy (FTIR), as well as open-circuit potential (OCP) and electrochemical impedance spectroscopy (EIS) methods. The ImAFM demonstrates the multiphase structure of the composite coating and a high compatibility between the doped PANI and alkyd matrix. The CV and EC-AFM results reveal a high electrochemical activity of the doped PANI in the composite coating as well as reversible redox reactions between the emeraldine salt (ES) and leuco emeraldine base (LB) forms. The Volta potential mapping of KFM demonstrates a strong self-healing ability of the doped PANI in air conditions. The good electrochemical connection between the fine network of PANI in the composite coating and metal surface underneath enable the occurrence of reversible redox reaction between the ES/LB forms of doped PANI and a concomitant release of dopant anions both in air and in 3 wt% NaCl solution as demonstrated by OCP and EIS results. These therefore lead to the strong passivation and self-healing effect of the composite coated on the carbon steel surface.